ASSESSMENT OF POLLUTION STATUS IN RIVER ACHENCOVIL, KERALA - Reeja Jose and Sanal Kumar, M.G (Journal of Aquatic Biology and Fisheries, 2014)
In the present study, the extent of pesticide and heavy metal pollution in Achencovil river was studied by taking water samples from three segments-upstream, midstream and downstream. The results showed that pesticide and heavy metal pollution was found to be highest at downstream, followed by mid stream. Most of them were totally absent or present in very low concentrations at upstream. Midstream possesses lesser amount of herbicide than downstream, while herbicides are not detectable at upstream. Only a trace amount of fungicides were detected from upstream. Moreover this study revealed that due to the impact of pesticides and heavy metals, most of the pollution tolerant species were present in mid and downstream segments while pollution intolerant were found to decrease in number in mid and downstream segments. However the pollution sensitive species was observed to be high in number at upstream.